Victorious Wallabies U.K. tour 1984 - Cooper, Terry; Murray, Peter A. (Peter Allen) (Waterloo, N.S.W. : Waterloo Press, 1985)
Annotation pending.
Foreword by Mark Ella.
Keywords: Wallabies (Rugby team); Rugby Union football -- Australia; Rugby Union football -- Great Britain; Sport - Football - Rugby union; United Kingdom / Great Britain (UK)